Preliminary investigation on antipyretic activity of Cuscuta Reflexa in rats - Sanjib Bhattacharya; Bodhisattva Roy (Wolters Kluwer Medknow Publications, 2010)
In present study, the antipyretic activity of aqueous and ethanol extracts from Cuscuta reflexa Roxb. (Cuscutaceae) was evaluated using Brewer's yeast induced pyrexia in rats. Both the extracts at 200 and 400 mg/kg body weight dose significantly (p < 0.05) reduced the increased rectal temperature. The extracts started reducing the elevated rectal temperature after 3 h of treatment in a dose related manner. At the dose of 400 mg/kg body weight the aqueous and ethanol extract reduced 79 % and 83.8 % respectively of the elevated rectal temperature as compared to reference drug paracetamol (96.5 %) after 6 h of treatment. It was therefore concluded that both the extracts of C. reflexa demonstrated antipyretic activity, the ethanol extract was found to be slightly potent than the aqueous extract.